2009
DOI: 10.1002/aqc.1046
|View full text |Cite
|
Sign up to set email alerts
|

Allometry and biomass distribution in replanted mangrove plantations at Gazi Bay, Kenya

Abstract: ABSTRACT1. This study reports above-ground biomass of 5 and 8 years old mangrove plantations in Kenya. Trees with stem diameter greater than 5.0 cm inside 100 m 2 sample plots were harvested, and then separated into stems (trunks), branches, leaves and prop roots.2. Mean above-ground biomass was calculated at 20.25 t dry matter ha À1 for Rhizophora mucronata Lam., 11.7 t dry matter ha À1 for Avicennia marina (Forsk.) Vierh., 6.7 t dry matter ha À1 for Sonneratia alba Sm. and 3.7 t dry matter ha À1 for Ceriops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…A review by Komiyama et al (2008) identified 13 species-specific and two common (i.e., multi-species) models for prediction of aboveground biomass of mangroves, while nine speciesspecific models and one common model were identified for belowground biomass. Additional studies on mangroves that developed models for prediction of biomass not present in this review also exist (e.g., Kairo et al 2009;Kauffman and Donato 2012;Sitoe et al 2014). With the exception of the models developed by Kairo et al (2009) in Kenya and Sitoe et al (2014) in Mozambique, most of the models have been developed for mangroves in Asia.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A review by Komiyama et al (2008) identified 13 species-specific and two common (i.e., multi-species) models for prediction of aboveground biomass of mangroves, while nine speciesspecific models and one common model were identified for belowground biomass. Additional studies on mangroves that developed models for prediction of biomass not present in this review also exist (e.g., Kairo et al 2009;Kauffman and Donato 2012;Sitoe et al 2014). With the exception of the models developed by Kairo et al (2009) in Kenya and Sitoe et al (2014) in Mozambique, most of the models have been developed for mangroves in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies on mangroves that developed models for prediction of biomass not present in this review also exist (e.g., Kairo et al 2009;Kauffman and Donato 2012;Sitoe et al 2014). With the exception of the models developed by Kairo et al (2009) in Kenya and Sitoe et al (2014) in Mozambique, most of the models have been developed for mangroves in Asia. The relatively few existing models for belowground biomass may be associated with the labor-intensive nature of sampling belowground biomass for mangrove tree species (Njana et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mangrove ecosystems also support high floral and faunal biodiversity [9,[12][13][14] and sequester significant amounts of CO 2 [15,16]. While numerous studies have measured above-ground biomass in mangrove trees (e.g., [17][18][19][20][21][22][23][24][25][26]), comparatively few have quantified above-and below-ground carbon (C) pools, including soil (i.e., [15,[27][28][29][30][31][32][33][34]); however, it is the deep, organic material enriched soils that contain the vast majority of C stocks [35][36][37][38]. Factoring in soil, mangroves have been found to be amongst the most carbon-dense forests in the tropics, with similar or greater above-and exceptionally larger below-ground stocks compared with the terrestrial systems reported in several studies [15,27,[32][33][34]39].…”
Section: Introductionmentioning
confidence: 99%